(untitled) (Research, Society and Development, 2021)
Introduction: Different mechanical behaviors in resistance training can result in certain changes in the cardiovascular system. Objective: To verify the acute behavior of the main cardiovascular variables (heart rate, blood pressure, and double product) when performing resistance training with mono and multiarticular exercises. Methods: 10 male subjects participated in the study (26 ± 4 years; 81 ± 6 kg; 1.77 ± 2 m; 23 ± 1 kg / m2). They performed a test and retest for 8RM in the bench press and crucifix exercises on the machine. After the loads were outlined, they performed the intervention with the exercises, initially with a monoarticular activation containing two sets of 12 repetitions with 50% of the load acquired in the 8RM test of each exercise, using an interval of 60 seconds between one set and another. Additionally, three sets of 8 repetitions (80% 8RM) were performed with an interval between sets of 120 seconds. The execution speed was determined at a moderate level (2s for concentric, 2s for eccentric). It was measured before and during (series 1, series two, and series 3. Named as moments) heart rate exercises using POLAR, model RS800CX Multisport® and blood pressure using OMRON M6 (HEM-7001- E) ®. Then, the double product was calculated using the formula [HR (bpm) X SBP (mmHg)]. Results: In the heart rate analysis, there was an intra-condition difference for moments 1, 2, and 3 compared to rest (p <0.000). In the inter-condition comparison, no differences were observed for rest (p = 0.994) and for moments 1, 2 and 3 (p> 0.999). In systolic blood pressure, intra-conditions, differences were observed for moments 1, 2, and 3 compared to rest (p <0.000). In the inter-condition comparisons, there were no differences between rest (p> 0.999), moment 1 (p = 0.714), 2 (p = 0.999) and 3 (p> 0.999). For diastolic blood pressure, intra conditions, for bench press no significant differences were found for moments 1 (p = 0.331), 2 (p = 0.505) and 3 (p = 0.505) when compared to rest. In the same way it was for the crucifix, wherein the comparison with rest, no difference was observed in moments 1 (p = 0.849), 2 (p = 0.195) and 3 (p = 0.105). In the same sense, no difference was also observed in the comparisons between conditions for rest (p> 0.999), moment 1 (p = 0.999), 2 (p = 0.989) and 3 (p = 0.948). Finally, the double product in intra-condition comparisons found differences between moments 1, 2, and 3 compared to rest (p <0.000). However, in the inter-condition comparisons, no difference was observed at rest (p = 0.999), moment 1 (p = 0.868), 2 and 3 (p> 0.999). Conclusion: It is suggested that resistance training composed of mono and multi-joint exercises offers differences in hemodynamic responses but without differences between the types of mechanics applied by the exercises. Therefore, these results offer a partiality of what can happen with heart rate, blood pressure, and double product.